The Differences of CPR duration between Shockable and Nonshockable Rhythms in Predicting the Benefit of Target Temperature Management. Issue 5 (20th May 2022) - Lin, Jr-Jiun; Huang, Chien-Hua; Chien, Yu-San; Hsu, Chih-Hsin; Chiu, Wei-Ting; Wu, Cheng-Hsueh; Wang, Chen-Hsu; Tsai, Min-Shan
ABSTRACT: Background: Among cardiac arrest (CA) survivors, whether the combination of duration of cardiopulmonary resuscitation (CPR) and shockable/nonshockable rhythms during resuscitation can help predict the benefit of targeted temperature management (TTM) remains un-investigated. Materials and methods: This multicenter retrospective cohort study enrolled 479 nontraumatic adult CA survivors with TTM and CPR duration < 60 min during January 2014 to June 2019 from the Taiwan network of targeted temperature ManagEment for CARDiac arrest (TIMECARD) registry. The differences of CPR duration between shockable and nonshockable rhythms in predicting outcomes in the studied population was evaluated. Results: We observed that 205 patients (42.8%) survived to hospital discharge and 100 patients (20.9%) presented favorable neurological outcomes at discharge. The enrolled patients were further re-classified into four groups according to shockable/nonshockable rhythms and CPR duration. Patients with shockable rhythms and shorter CPR duration had better survival-to-discharge (adjusted odds ratio [OR] = 2.729, 95% confidence interval [CI] = 1.384–5.383, P = 0.004) and neurological recovery (adjusted OR = 9.029, 95%CI = 3.263–24.983, P   <  0.001) than did those with nonshockable rhythms and longer CPR duration. Conclusion: The CPR duration for predicting outcomes differs between CA patients with shockable and nonshockable rhythms. The combination of shockable/nonshockable rhythms and CPR duration may help predict the prognosis in CA survivors undergoing TTM.